Pengukuran Persepsi Manfaat Dan Persepsi Kemudahan Terhadap Sikap Serta Dampaknya Atas Penggunaan Ulang Online Shopphing Pada E-Commerce - Iwan Sidharta; Rahmahwati Sidh (STMIK Mardira Indonesia, Bandung, 2014)
The development of e-commerce in Indonesia is growing rapidly, resulting in the change of people's behavior in conducting online transactions. This study aims to determine perceived usefulness, perceived of use, attitude, and intention to use student STMIK Mardira Indonesia Bandung towards online shopping behavior in e-commerce. Exploratory research methods of data analysis techniques using Structural Equation Modelling (SEM), component-based Partial Least Squares (PLS). The number of respondents were 60 active students who never transact online through e-commerce, with the data collection technique purposive sampling. Results of the study indicate where perceived usefulness, perceived of use significantly influence the attitude of students STMIK in online shopping, as well as a significant effect also on the intention to use. Keywords: perceived usefulness; perceived of use; attitude; intention to use